Prehospital Efficacy and Adverse Events Associated with Bolus Dose Epinephrine in Hypotensive Patients During Ground-Based EMS Transport. Issue 5 (23rd October 2020) - Patrick, Casey; Ward, Brad; Anderson, Jordan; Fioretti, Joe; Rogers Keene, Kelly; Oubre, Carri; Cash, Rebecca E.; Panchal, Ashish R.; Dickson, Robert
Abstract: Background: The utility and efficacy of bolus dose vasopressors in hemodynamically unstable patients is well-established in the fields of general anesthesia and obstetrics. However, in the prehospital setting, minimal evidence for bolus dose vasopressor use exists and is primarily limited to critical care transport use. Hypotensive episodes, whether traumatic, peri-intubation-related, or septic, increase patient mortality. The purpose of this study is to assess the efficacy and adverse events associated with prehospital bolus dose epinephrine use in non-cardiac arrest, hypotensive patients treated by a single, high-volume, ground-based Emergency Medical Services (EMS) agency. Methods: This is a retrospective, observational study of all non-cardiac arrest EMS patients treated for hypotension using bolus dose epinephrine from September 12, 2018 through September 12, 2019. Inclusion criteria for treatment with bolus dose epinephrine required a systolic blood pressure (SBP) measurement <90mmHg. A dose of 20mcg every two minutes, as needed, was allowed per protocol. The primary data source was the EMS electronic medical record. Results: Forty-two patients were treated under the protocol with a median (IQR) initial SBP immediately prior to treatment of 78mmHg (65-86) and a median (IQR) initial mean arterial pressure (MAP) of 58mmHg (50-66). The post-bolus SBP and MAP increased to 93mmHg (75-111) and 69mmHg (59-83), respectively. The two most common patient presentations requiring protocol use were altered mental status (55%) and respiratory failure (31%). Over one-half of the patients treated required both advanced airway management (62%) and multiple bolus doses of vasopressor support (55%). A single episode of transient severe hypertension (SBP>180mmHg) occurred, but there were no episodes of unstable tachyarrhythmia or cardiac arrest while en route or upon arrival to the receiving hospitals. Conclusion: These preliminary data suggest that the administration of bolus dose epinephrine may be effective at rapidly augmenting hypotension in the prehospital setting with a minimal incidence of adverse events. Paramedic use of bolus dose epinephrine successfully increased SBP and MAP without clinically significant side effects. Prospective studies with larger sample sizes are needed to further investigate the effects of prehospital bolus dose epinephrine on patient morbidity and mortality.